A discrete model of a transmission line and the Faber polynomials - Kurbatov, Vitalii (Eurasian Mathematical Journal, 2024)
The spectrum of the matrix coefficient A corresponding to a discrete model of a transmission line often has the shape of a cross. The paper suggests to use the Faber series instead of the Taylor series when calculating the matrix exponential of A. This method can enlarge the accuracy and speed up calculations